2021
DOI: 10.1071/an20468
|View full text |Cite
|
Sign up to set email alerts
|

Tannins from

Abstract: Context Tannins are polyphenolic compounds found in legumes, trees and forage shrubs, such as Mimosa tenuiflora, and form hydrogen bonds with proteins. Aims The objective of the present study was to determine the optimal dietary concentration of natural tannins from M. tenuiflora for enhancing intake, digestibility, nitrogen (N) and tannin physiological balance, performance, carcass traits and commercial cuts of lambs. Methods Forty-eight uncastrated Santa Ines lambs were distributed between two experiments,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 48 publications
0
1
0
Order By: Relevance
“…Two factors can explain this result. One of them would be the high concentration of condensed tannins present in catingueira leaves [ 27 ], since high tannin concentrations markedly reduced intake, changing the acceptability of a food [ 28 ]. Gonzaga Neto et al [ 29 ] observed that the DMI of Morada Nova sheep linearly decreased due to the increased inclusion of catingueira hay in the animals’ diet.…”
Section: Discussionmentioning
confidence: 99%
“…Two factors can explain this result. One of them would be the high concentration of condensed tannins present in catingueira leaves [ 27 ], since high tannin concentrations markedly reduced intake, changing the acceptability of a food [ 28 ]. Gonzaga Neto et al [ 29 ] observed that the DMI of Morada Nova sheep linearly decreased due to the increased inclusion of catingueira hay in the animals’ diet.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the Mimosa tenuiflora hay presents varying concentrations of tannins, ranging from 0.67 g/kg [4] to 1.8 g/kg DM [5]. These tannins can affect the intake and digestibility of dry matter [6], crude protein [7], and carbohydrates [8].…”
Section: Introductionmentioning
confidence: 99%